Author Correction: Small-wedge synchrotron and serial XFEL datasets for Cysteinyl leukotriene GPCRs - Marin, Egor; Luginina, Aleksandra; Gusach, Anastasiia; Kovalev, Kirill; Bukhdruker, Sergey; Khorn, Polina; Polovinkin, Vitaly; Lyapina, Elizaveta; Rogachev, Andrey; Gordeliy, Valentin; Mishin, Alexey; Cherezov, Vadim; et al. (Scientific data, 2020)
A Correction to this paper has been published: https://doi.org/10.1038/s41597-020-00759-w.